Postoperative analgesia with epidural opioids after cesarean section: Comparison of sufentanil, morphine and sufentanil-morphine combination - Kalpana S Vora; Veena R Shah; Bhadresh Patel; Geeta P Parikh; Bina P Butala (Wolters Kluwer Medknow Publications, 2012)
Background: Epidural analgesia with opioid provides good control of postoperative pain in cesarean section, thereby improving the mother's ability to mobilize and interact with her newborn infant. Aim: The aim of this study is to evaluate and compare the analgesic actions and side effects of epidural analgesia with sufentanil, morphine or combination of the two after cesarean section. Materials and Methods: 60 women undergoing elective cesarean section were allocated into three groups of 20 each in a randomized blinded fashion. Epidural analgesia was administered with sufentanil 50 mcg in Group S; morphine 4 mg in Group M; and, a combination of sufentanil 25 mcg and morphine 2 mg was used in Group SM. Analgesic efficacy in terms of onset of action and duration of analgesia was assessed by using the Visual Analog Scale (0 to 10 cm) for 24 hours. Number of opioid doses needed in 24 hours was noted. Side effects like respiratory depression /excessive sedation, pruritus and nausea were recorded. Results: Onset of action were at 7.6 ± 1.5 minutes in group S, 67.6 ± 1.5 minutes in group M and 12.2 ± 2.6 minutes in group SM. Duration of analgesia was longer in group M 17.5 ± 1.9 hours and SM 13.8 ± 1.6 hours than in group S 5.2 ± 1.2 hours. More doses of analgesia were required in group S compared to group M and SM. Side effects were comparable in the three groups. Conclusion: Epidural administration of a combination of sufentanil and morphine offered the advantage of faster onset of action and longer duration of analgesia as compared to the two drugs administered alone.